O conceito aboutness na organização e representação do conhecimento - Guedes, Emanuel Guedson Ferreira [UNESP] (2009)
The subject determination that occurred in the analytical stage of a document submitted to the subject analysis, is a field of study in need of methodologies that can help the professional readers in the selection of concepts that provide the subsidies to elaborate documentaries products. Thus, studies on the concept Aboutness have acquired a clear role in the documentary field studies in order that the process of assigning terms and concepts from the documentary reading should adequately summarize the information content of the document by making the procedure a key moment for all subsequent stages of the process. Thus, information science has sought in other fields, subsidies to help in the subject analysis in order to assist in your understanding in accordance with the purpose of their representation in an information system. We approach the literature of information science around the concept of aboutness with a purpose to better understanding this conception of subject analysis and both are explored in addition to the related literature, four major national journals in the field, selecting items that have submitted or discussed this concept. It was found that the term aboutness has been translated by atinência, tematicidade and sobrecidade, and there was no consensus on one of three terms, however, while sobrecidade has fallen into disuse, tematicidade and atinência remain in use. Furthermore, although little explored in portuguese, this concept has conceptual implications for the area, which can influence the theoretical development of processes to identify the subject by seeking an approach that aims not only to identify the aboutness inherent in the document, but also aboutness assigned by the indexer or user, also handled by meaning (significado), and thus admits that even with the possibility of assigning different meanings and interpretations of a document that has an inherent and fundamental issue that does not change.